Analysis of biochemical laboratory values to determine etiology and prognosis in patients with subarachnoid hemorrhage: a clinical study. (1st February 2019) - Ogden, Mustafa; Bakar, Bulent; Karagedik, Mustafa Ilker; Bulut, Ibrahim Umud; Cetin, Cansel; Aydin, Gulcin; Kisa, Ucler; Ozveren, Mehmet Faik
ABSTRACT: Objectives : The aim of this study was to establish prognostic and predictive markers in patients with subarachnoid hemorrhage (SAH) using simple laboratory methods. Methods : A retrospective examination was made of patients with SAH diagnosed secondary to isolated head trauma, isolated anterior communicating artery aneurysm rupture, and angiography-negative SAH. Age, gender, Glasgow Coma Scale (GCS) scores, and Fisher's grade scores, Glasgow Outcome Scale (GOS) scores, leukocyte count, neutrophil count, lymphocyte count, platelet count, neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio results (PLR) were evaluated. Results : NLR and PLR values, which were similar in patients with spontaneous SAH, were significantly high in patients with traumatic SAH. NLR and PLR values could be 80% sensitive and 75% specific for distinguishing traumatic SAH from spontaneous SAH. Eosinophil count was lower in patients with angiography-negative SAH and patients with aneurysmal SAH than in patients with traumatic SAH. Initially measured GCS score, Fisher's grade score, eosinophil, neutrophil and lymphocyte counts could be prognostic in all patients with SAH. Moreover, it was concluded that the initially measured number of eosinophils might be directly related to patient prognosis. The eosinophil count was generally found to be high in traumatic SAH patients and it was observed that this parameter could be predictive for these patients. Lymphocyte count and NLR values could be prognostic markers in patients with angiography-negative SAH. Conclusion : NLR, PLR and eosinophil count values could be predictive for etiological factors (traumatic SAH or spontaneous SAH) of patients who were admitted unconscious to the emergency room with SAH detected on radiological imaging.